Analysis of the Impact of External Debt on Health in an Emerging Asian Economy: Does FDI Matter? - Ma, Yechi; Hu, Mengyun; Zafar, Quratulain (Frontiers in Public Health, 2022)
In this study, our main objective is to find the impact of FDI and external debt on health outcomes in emerging Asian economies from 1991-2019. To that end, we have collected data for seven economies: Bangladesh, Malaysia, Philippines, Thailand, Sri Lanka, China, and India. We have relied on the panel ARDL (PARDL) method for empirical analysis. The study's findings confirmed that the debt has increased infant mortality and decreased life expectancy in emerging Asian economies in the long run. On the other side, the FDI causes infant mortality to fall and life expectancy to rise in the long run in emerging Asian economies. Similarly, the health expenditures also reduced the infant mortality rate, though the impact is insignificant, and improved the life expectancy in emerging Asian economies. The causal analysis confirmed the two-way causality between health expenditure, infant mortality, and health expenditure and debt.